Islamic Finance Ethical Underpinnings, Products, and Institutions - Hassan, Abul (Springer International Publishing, 2018)
Islamic finance often faces numerous challenges in a dynamic marketplace. This book aims to discuss contemporary issues and challenges in Islamic finance to inform discussions surrounding the governance system, the Islamic legal system, prudential regulations, Islamic home financing, and Islamic microfinance. Furthermore, corporate social responsibility (CSR), Islamic accounting, risk management, Basel Accord, and Shari'ah governance systems are discussed in the book. Despite the relevance of these issues in Islamic finance, only a few reference sources exist. This book will provide a guide for academics, students, and banking professionals to acquaint them with the theory and practice of Islamic finance, filling a needed gap.